Pelatihan Mitigasi dan Tanggap Darurat untuk Masyarakat Desa - Irfan Zayyadu (Lembaga Publikasi Ilmiah Nusantara, 2026)
Flood Mitigation and Emergency Response Training for Rural Communities in Facing Flood Disasters is a strategic initiative aimed at enhancing community capacity to manage the increasing risk of floods caused by climate change, environmental degradation, and geographical vulnerability. Recurrent flooding not only threatens lives but also disrupts the socio-economic activities of rural communities, thereby necessitating participatory, community-based capacity-building efforts. This training program is designed to equip community members with knowledge about the causes of flooding, water flow patterns, identification of flood-prone areas, and mitigation techniques that can be implemented individually and collectively, such as maintaining drainage systems, reforesting critical areas, and developing risk-based spatial planning. In addition to mitigation aspects, the training emphasizes emergency preparedness through the development of evacuation procedures, the establishment of village volunteer teams, the management of assembly points and evacuation routes, and the use of basic safety equipment. The training methods are implemented in an integrated manner through lectures, group discussions, participatory risk mapping, field simulations, and learning evaluations. The results indicate a significant improvement in the community’s ability to recognize early warning signs of flooding, respond appropriately to emergency situations, and organize collective actions to reduce disaster impacts. Overall, this initiative contributes to the formation of more resilient, adaptive, and self-reliant rural communities capable of integrating local knowledge with disaster risk management principles. With strengthened capacity, communities are expected to reduce vulnerability and enhance village resilience against current and future flood threats.